SISTEM PENDUKUNG KEPUTUSAN PENERIMA BEASISWA PRESTASI DENGAN METODE SIMPLE ADDITIVE WEIGHT - Endang Widia Astuti (SPIRIT, 2016)
In accordance with regulations set by the school to receive a scholarship, the necessary criteria to determine who will be chosen to receive a scholarship. Distribution of scholarships is done by several agencies to hesomeone less fortunate or achievement during their studies. To assist in determining a person determining the eligible then takes a decision support system. These criteria are verified using Fuzzy MADMKeywords: FMADM, CRITERIA,SAW,BEASISWA PRESTASI